A novel link between FMR gene and the JNK pathway provides clues to possible role in malignant pleural mesothelioma. Issue 1 (19th August 2015) - Srivastava, Ajay
Abstract : Malignant pleural mesothelioma (MPM) is an aggressive form of thoracic cancer with poor prognosis. While some studies have identified the molecular alterations associated with MPM, little is known about their role in MPM. For example, fragile X mental retardation ( FMR ) gene is up‐regulated in MPM but its role in MPM is unknown. Here, utilizing Drosophila genetics, I investigate the possible role FMR may be playing in MPM. I provide evidence which suggests that FMR may contribute to tumorigenesis by up‐regulating a matrix metalloprotease (MMP) and by degrading the basement membrane (BM), both important for tumor metastasis. I also demonstrate a novel link between FMR and the JNK pathway and suggest that the effects of FMR in MPM could in part be mediated by up‐regulation of the JNK pathway. Abstract : The FMR gene is up‐regulated in malignant pleural mesothelioma. Overexpression of dFMR causes overexpression of matrix metalloprotease. Overexpression of dFMR induces basement membrane degradation. Overexpression of dFMR results in upregulation of the JNK pathway.